2020
DOI: 10.1111/jac.12431
|View full text |Cite
|
Sign up to set email alerts
|

Chilling stress tolerance of two soya bean cultivars: Phenotypic and molecular responses

Abstract: Soya bean [Glycine max (L.) Merr.] is an important legume crop with a significant worldwide production (Govindasamy et al., 2017), accounting for 340 million metric tons (mmt) in 2017. Exceptionally high protein (40%) and oil (20%) content make soya bean an outstanding source of nutrition that is used in a number of food products for humans, as well as in animal feeds. In addition, oil extracted from soya bean seeds can be used in the production of biofuels (Zhang, Pan, & Stellwag, 2008). All these benefits ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
0
6
0
2
Order By: Relevance
“…Our approach based on the use of high‐throughput methods broadens the knowledge of mode of action of miRNAs in soybean plants. A previous study showed that cold stress influences the growth of two tested varieties, namely Augusta and Fiskeby V, which was observed as phenotypic changes (Kuczyński et al, 2020). It was also shown that under chilling stress, the expression levels of several miRNAs (miR169, miR319, miR397 and miR398) and their target genes had changed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our approach based on the use of high‐throughput methods broadens the knowledge of mode of action of miRNAs in soybean plants. A previous study showed that cold stress influences the growth of two tested varieties, namely Augusta and Fiskeby V, which was observed as phenotypic changes (Kuczyński et al, 2020). It was also shown that under chilling stress, the expression levels of several miRNAs (miR169, miR319, miR397 and miR398) and their target genes had changed.…”
Section: Discussionmentioning
confidence: 97%
“…These interactions comprise mRNA cleavage based on the binding to complementary sequences within its target genes as well as translation inhibition by restriction of the ribosome binding process (Bartel, 2004). To date, a number of miRNAs in soybean has been reported to be associated with response to abiotic and biotic stresses such as drought, salinity (Liu et al, 2016), phosphate starvation (Xu et al, 2013), cold (Kuczyński et al, 2020) and cyst nematode infection (Li et al, 2012). However, the involvement of miRNAs in the chilling stress response in soybean is poorly explained and needs further investigation.…”
mentioning
confidence: 99%
“…Several studies conducted on soybeans have shown that Circular (circRNA)- and MicroRNA (miRNA)-based gene regulation were also involved in coordinating soybean responses to cold stress in post-transcriptional regulation [ 6 , 73 , 74 , 75 , 76 , 77 , 78 ]. In cold-treated soybean plants, miR166u, miR171p, miR2111f, and miR169c may regulate different targets in mature nodules through mRNA degradation [ 6 ].…”
Section: Soybean Cold Responsive Regulators and Associated Cold Regul...mentioning
confidence: 99%
“…Сорти української селекції мають безліч переваг, вони високопродуктивні, посухостійкі, адаптовані до наших місцевих умов, генетично не модифіковані, за урожайністю і вмістом білка не поступаються іноземним, а інколи мають певні переваги [2,4,5]. Кожен сорт потребує вивчення оптимальних параметрів агротехнічних прийомів, серед яких важливе значення належить строкам сівби та стимуляторам росту, що особливо важливо в умовах зміни клімату [6][7][8].…”
Section: вступunclassified